La gamificación como estrategia de aprendizaje de geometría en estudiantes de octavo año de Educación General Básica - Padilla Ortiz, Yadira Nataly (2024)
Gamification, as a learning technique in the teaching of mathematics, plays an important role in the learning process of students. The objective of this research work is to design a didactic guide for the use of gamification as a methodological strategy in the geometry learning process for students in the eighth year of General Basic Education at the "Fernando Daquilema" Educational Unit in the 2023-2024 academic period. The research methodology chosen to support this work has a quantitative approach, non-experimental design, two types of research: field, transversal and descriptive, propositional scope. When analyzing the results obtained through the application of the instruments for the collection and analysis of information such as: observation sheet and questionnaire, it was found that students showed interest and motivation to learn geometry with the use of gamification and it was concluded that this learning technique is of great importance in higher basic education, so it is recommended the application of game mechanisms in the learning process of students.